Neurofibromatosis type 1 (Nf1)‐mutant mice exhibit increased sleep fragmentation. (4th January 2019) - Anastasaki, Corina; Rensing, Nicholas; Johnson, Kevin J.; Wong, Michael; Gutmann, David H.
Abstract: Neurofibromatosis type 1 (NF1) is a neurodevelopmental disorder in which affected children and adults are at a higher risk of sleep disorders. In an effort to identify potential sleep disturbances in a small animal model, we used a previously reported Nf1 conditional knockout ( Nf1 CKO ) mouse strain. In contrast to Nf1 mutant flies, the distribution of vigilance states was intact in Nf1 CKO mice. However, Nf1 CKO mice exhibited increased non‐REM sleep (NREM)‐to‐wake and wake‐to‐NREM transitions. This sleep disruption was accompanied by decreased bout durations during awake and NREM sleep states under both light and dark conditions. Moreover, Nf1 CKO mice have higher percentage delta power during awake and NREM sleep states under all light conditions. Taken together, Nf1 CKO mice phenocopy some of the sleep disturbances observed in NF1 patients and provide a tractable platform to explore the molecular mechanisms governing sleep abnormalities in NF1.